Comparative histology of the vocal sac in three species of hylid frogs with comments on its functional correlates - Bueno, Natalia Ferreira; Elias-Costa, Agustín J.; Baêta, Délio [UNESP]; Fragoso-Moura, Evelise N. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
The vocal sacs of frogs are elastic structures responsible for the circulation of air during vocalization, amplifying the sounds produced by these animals during multimodal communication. Vocal sacs present a wide array of morphologies among species and may be single, paired, or absent in adult males. Most studies on vocal sacs in Anura deal with their external morphology, and not with their internal structure, which has been explored in only a handful of species. The aim of this study was to assess vocal sac structure in three hylid species, Dendropsophus haddadi, D. elegans, and Scinax fuscovarius, using histological techniques. These species differ greatly in the degree of development and histological properties of the gular skin and submandibular musculature. In particular, elastic fibers are abundant in the thick m. interhyoideus and the relatively tight gular skin of S. fuscovarius. In contrast, in both species of Dendropsophus (although more evident in D. elegans), the m. interhyoideus is extremely thin and expanded, with a negligible number of elastic fibers that appear as a loose, pleated sheet when deflated. We analyzed videos of calling males of the three species and their close relatives, which show two different patterns of inflation/deflation. These patterns are strongly correlated with the histological properties of the vocal sac wall. The three species have different vocal sac shapes and rely differently on elasticity for vocal sac function.
Histologia comparativa do saco vocal de três espécies de hilídeos com comentários sobre suas correlações funcionais.
Keywords: Animal histology; Anura; Elastic fibers; Morphology; Vocal slits; Vocalization